PENGARUH DISIPLIN DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI PADA KECAMATAN PAGEDANGAN KABUPATEN TANGERANG - Saepudin; Savitri, Shela Indah (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the influence of discipline and the physical work environment on employee performance in Pagedangan District, Tangerang Regency, both partially and simultaneously. This research method uses quantitative methods with a population and sample of 60. The data analysis techniques used are data instrument tests, classical assumption tests, linear regression tests, correlation coefficient tests, determination tests and hypothesis tests. Based on the research results, discipline has a significant effect on employee performance with a coefficient of determination value of 37.4% and hypothesis testing obtained a calculated t value > t table or (2.165 > 2.001). The physical work environment has a significant effect on employee performance with a coefficient of determination value of 38.1% and the hypothesis test obtained a calculated t value > t table or (2.313 > 2.001). Discipline and the physical work environment simultaneously have a significant effect on employee performance with the regression equation Y = 9.753 + 0.362 Hypothesis testing obtained F count > F table or (21.326 > 3.16).